How Mexico lost its foreign exchange reserves - Atkeson, Andrew 1961-; Ríos-Rull, José-Víctor (NBER working paper series, 1995)
In standard models of the balance of payments, crises occur when investors begin to doubt the credibility of the government's commitment to its exchange rate policy. In this paper, we develop an alternative model in which balance of payments crises occur even if the credibility of government fiscal, monetary, and exchange rate policies is never in doubt. In this alternative model, international lending is constrained by the risk of repudiation. Balance of payments crises occur when the government and citizens of a country hit their international borrowing constraints. Our model is broadly consistent with events in Mexico from 1987-1995. More generally, our model suggests that countries which undertake sweeping macroeconomic and structural reforms should expect to face a balance of payments crisis when they exhaust their access to international capital inflows.